The accumulation of metal runoff from acidic sulphate soils in two avian predators, white-tailed eagle (Haliaeetus albicilla) and great cormorant (Phalacrocorax carbo) - Vainio, Riikka (My University, 2018)
Acidic sulphate soils are one of the largest sources of metal contamination in Finland, exceeding in some cases industrial emissions. Sulphate soils occur naturally in the Finnish coastal areas, but anthropogenic land modification and land rising causes the metals and metalloids in the soil mobilize and end up in water bodies with runoff. Metal leaches from sulphate soils are harmful to aquatic organisms, but the concentrations and accumulation of metals from sulphate soils in apex avian species has not been studied. Using inductively coupled plasma -mass spectrometry, concentrations and spatial trends of 17 metals and metalloids associated with sulphate soils were analysed from the blood of nestlings of white-tailed eagles and great cormorants collected from sulphate soil and control areas in the western Finnish coast. For most metals, there were no differences in blood concentrations between control and sulphate soil areas, except for the arsenic concentrations in white-tailed eagles, which were higher in the sulphate soil areas, and lithium concentrations of cormorants, which were higher in the control areas. The concentrations of most metals were within background levels, not known to cause toxic effects. Concentrations of mercury, cadmium and lead were at the level of mild sublethal toxicity. Concentrations of several elements correlated between species. Latitudinal trends and intraspecies correlations of metals were also observed. The results indicate, that the white-tailed eagles and great cormorants do not get their metal burden from the sulphate soils, and that metal contamination and their accumulation into apex species varies along the Finnish coast.
Keywords: white-tailed eagle, great cormorant, acidic sulphate soils, metals